The Map of Watchful Architecture - Garrett Carr (EchoGéo)
The international border between Northern Ireland and the South (the Republic of Ireland) came into beingin 1922, but there are many important historical antecedents to the notion and expression of spatial separation in this borderland. The author identifies historical precedents and links them to recent defensive features in order to generate a 'map of watchful architecture' that includes recent and much older elements.